Indium-Doped Zinc Oxide Thin Films as Effective Anodes of Organic Photovoltaic Devices - Ziyang Hu; Baochen Jiao; Jianjun Zhang; Xiaodan Zhang; Ying Zhao (International Journal of Photoenergy)
Indium-doped zinc oxide (IZO) thin films were prepared by low-cost ultrasonic spray pyrolysis (USP). Both a low resistivity (3.13×10−3 Ω cm) and an average direct transmittance (400∼1500 nm) about 80% of the IZO films were achieved. The IZO films were investigated as anodes in bulk-heterojunction organic photovoltaic (OPV) devices based on poly(3-hexylthiophene) and [6,6]-phenyl C61-butyric acid methyl ester. The device fabricated on IZO film-coated glass substrate showed an open circuit voltage of 0.56 V, a short circuit current of 8.49 mA cm-2, a fill factor of 0.40, and a power conversion efficiency of 1.91%, demonstrating that the IZO films prepared by USP technique are promising low In content and transparent electrode candidates of low-cost OPV devices.